Origin and evolution of papillomavirus (onco)genes and genomes - Willemsen, Anouk (Philos Trans R Soc Lond B Biol Sci, 2019)
Papillomaviruses (PVs) are ancient viruses infecting vertebrates, from fishes to mammals. Although the genomes of PVs are small and show conserved synteny, PVs display large genotypic diversity and ample variation in the phenotypic presentation of the infection. Most PV genomes contain two small early genes E6 and E7. In a bunch of closely related human papillomaviruses (HPVs), the E6 and E7 proteins provide the viruses with oncogenic potential. The recent discoveries of PVs without E6 and E7 in different fish species place a new root on the PV tree, and suggest that ancestral PVs consisted of the minimal PV backbone E1-E2-L2-L1. Bayesian phylogenetic analyses date the most recent common ancestor of the PV backbone to 424 million years ago (Ma). Common ancestry tests on extant E6 and E7 genes indicate that they share a common ancestor dating back to at least 184 Ma. In AlphaPVs infecting Old World monkeys and apes, the appearance of the E5 oncogene 53–58 Ma concurred with (i) a significant increase in substitution rate, (ii) a basal radiation and (iii) key gain of functions in E6 and E7. This series of events was instrumental to construct the extant phenotype of oncogenic HPVs. Our results assemble the current knowledge on PV diversity and present an ancient evolutionary timeline punctuated by evolutionary innovations in the history of this successful viral family. This article is part of the theme issue ‘Silent cancer agents: multi-disciplinary modelling of human DNA oncoviruses’.